Analisa Bangkitan Perjalanan di Wilayah Komplek Perumahan Safira Kota Jambi - Das, Amsori M; Setiawan, Ari; Wahyudi, Danial (Universitas Batanghari Jambi, 2024)
From data from BPS (Central Statistics Agency) Jambi City, the population of Jambi City in 2022 is 619,553 people with an area of 205.38 km2, has 11 sub-districts. Safira Housing is one of the housing complexes located in Talang Bakung Village, Paal Merah District, Jambi City. Population Safira housing ± 455 people. The increase in trips made by a number of Safira housing communities will cause traffic jams during peak hours such as when leaving and returning from work. This research method uses multiple linear regression with independent variables consisting of the number of family members X1, the number of family members who work X2, number of family members attending school x3, with trip generation as variable Y and then analyzed using the SPSS application. The variable that has a dominant influence on the dependent (dependent) variable is based on the standardized coefficient beta value, namely the variable number of family members attending school/college (X3), number of family members (X1), and number of working family members (X2). The trip generation analysis model at Safira Housing is: Y 2.257 + 0.275 X1 + 0.227 X2 + 0.528 From this model, the factors that influence the generation of Safira Housing trips are obtained, namely the number of family members (X1), the number of family members who work (X2), the number of family members who go to school/college (X3). Based on the R Square value of 0.621, this means that 62.1% of trip generation at Safira Housing is explained by the independent variables in the form of number of family members, number of family members working, number of family members attending school/university.